Penerapan Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi pada Kurikulum Merdeka di Sekolah Dasar - Sholihah Ummi Nirmala; Anggita Agustina; Siti Robiah; Ayu Ningsi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study aims to describe the application, its advantages and disadvantages, and possible solutions for using information and communication technology-based learning media in the independent curriculum of elementary schools. The research is qualitative, using phenomenological analysis. Data was collected through interviews, observation, and documentation, and analyzed using data reduction, presentation, and conclusion. The study revealed that 1) the independent curriculum has been implemented, but differentiated learning has not yet been fully realized. Teachers lack technology skills and still rely on the lecture method. 2) The advantage of the application is that it allows teachers to assign material for students to study independently, but the drawback is that some teachers and students struggle with operating the required technology, reducing effective learning time. 3) Solutions to this challenge include teacher training, seeking additional materials online, using game-based learning media, and encouraging students to practice using the application at home before learning.